2011
DOI: 10.1017/s1751731110002715
|View full text |Cite
|
Sign up to set email alerts
|

Selection for nutrients by pregnant goats on a microphyll desert scrub

Abstract: The behavioral consequences of pregnancy in goats were studied to test the hypothesis that pregnant females on rangeland select a diet richer in nutrients once the demands of gestation increase, and that nutrient content in goat diets changes with the grazing season. A total of 12 mature mixed breed goats either pregnant ( n 5 6) or non-pregnant ( n 5 6) were used during the dry period (February to May). Dietary samples obtained from the oral cavity of grazing goats (restrained with a short light rope permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Therefore, when feed supply to the fetuses reduces, the birth weight of kids also reduces. The result of this study supports the hypothesis that regardless of parity, litter weight in lactating goats increased at a reduced rate with an increase in litter size (Mellado et al, 2011). This study is consistent with a study conducted on black Bengal goats by Paul et al (2014), where the result showed that birth weight of kids was significantly affected by litter size (p<0.01).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, when feed supply to the fetuses reduces, the birth weight of kids also reduces. The result of this study supports the hypothesis that regardless of parity, litter weight in lactating goats increased at a reduced rate with an increase in litter size (Mellado et al, 2011). This study is consistent with a study conducted on black Bengal goats by Paul et al (2014), where the result showed that birth weight of kids was significantly affected by litter size (p<0.01).…”
Section: Discussionsupporting
confidence: 91%
“…Studies commonly found that herbivores preferentially select plant species relatively high in nutrients 16 . However, it was not the case with L. chinensis , as it had a higher CP content than C. squarrosa and C. duriuscula but the lambs with longer access time at pasture did not focus their grazing on it, even when nutrient levels were highest in July.…”
Section: Discussionmentioning
confidence: 99%
“…This perennial xerophytic species was chosen by the goats, regardless of its cover and season of the year. This plant can account for up to 15% of the diet (Mellado et al, 2011). The resistance of Larrea tridentata to drought -along with its moderate levels of protein (104-117 g kg 1 DM; Table 1) and its continuous metabolic activity under extreme drought conditions (Allen et al, 2008)seems to be the attribute that makes it appealing to goats.…”
Section: Resultsmentioning
confidence: 99%